Impact Non-Oil and Gas Exports and Oil and Gas Exports on The Position of Indonesia Foreign Exchange Reserves - Pudji Djatmiko; Nugroho SBM (Faculty of Economics, State University of Jakarta., 2019)
This study aims to determine and analyze the effect of Non-Oil and Gas Exports and Oil and Gas Exports on the Position of Indonesian Foreign Exchange Reserves partially in the period 1996 to 2017 which employs 22 data annually using SPSS 24. The dependent variable in this study is Indonesia's foreign exchange reserves, while the independent variables are non-oil and gas exports and oil and gas exports. To see the effect of independent variables on the dependent variable, the researcher did multiple linier regression analysis. Based on the results of this research, it is known that partially non-oil and gas export and oil and gas export have a positive and significant impact on Indonesia's foreign exchange reserves.